The insecticidal activity of methyl benzoate against Tribolium castaneum by transcriptomic analysis and in-silico simulation. (May 2022) - Wang, Lei; Ding, Sai-sai; Zhang, Ning-jing; Lu, Yujie; Geng, Xueqing; Zhao, Zongpei
Abstract: Plant-derived methyl benzoate (MB) is a scent and aroma released by many flowers and fruits. Recently, MB has emerged as an alternative pesticide to control insect pests. However, the molecular mechanisms of insects' responses to MB remain to be investigated. MB exhibited a dose-dependent toxicity to all the developmental stages of Tribolium castaneum (Herbst). Based on the PoloPlus analysis of the lethal median concentration (LC50 ) of contact/fumigant toxicity for eggs, larvae, pupae, and adults, our study indicated that larvae appeared to be most resilient to MB, and eggs were the most susceptible life stage. Next, we used RNA-seq method to analyze MB-response genes in T. castaneum larvae. Total of 1061 differentially expressed genes (DEGs) were identified, and analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. The transcriptional expressions of identified genes were validated by real-time quantitative polymerase chain reaction (RT-qPCR). RNA-seq results indicated that genes that involved chitin biosynthesis, energy metabolism, nervous action, and metabolic detoxification were shown to be differentially expressed. Notably, gene expressions of cathepsin (B and L type), and total gut proteolytic activity were inhibited in MB-contacted/fumigated larvae, suggesting that MB exposure led to the suppression of digestive activity. And molecular dynamics results indicated that OBP99b could stably bind with MB. This research will enrich our knowledge of the molecular mechanisms of beetle's response to MB, and facilitate us to develop an efficient strategy to control insect pests. Highlights: Methyl benzoate (MB) is a fumigant candidate to control Tribolium castaneum. Eggs were most susceptible, and late instar larvae were the most tolerant to MB. RNA-seq method was used to analyze MB-response genes in T. castaneum larvae. The transcriptional expressions of identified genes were validated by RT-qPCR. Molecular dynamics analysis of potential receptors with MB.